2001
DOI: 10.1161/01.hyp.37.6.1351
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Function in Hypertensive and Normotensive Subjects

Abstract: Abstract-Baroreceptor reflex sensitivity (BRS) has been found lower and heart rate variability (HRV) parasympathetic markers have been found higher in healthy women than in healthy men. Thus, in the present study we hypothesized gender differences in the autonomic function among hypertensive subjects. Forty-one hypertensive patients and 34 normotensive subjects, age 53Ϯ1 years, were examined. Four weeks after cessation of antihypertensive therapy, HRV was assessed in 24-hour Holter ECGs, and BRS was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 44 publications
(63 reference statements)
10
84
2
3
Order By: Relevance
“…This test produces a sensitive specific and reproducible indirect measure of autonomic activity on cardiac function In our study the demographic characteristics of the Indians and NRI subjects are well balanced and individuals in both groups did not differ significantly in age 16 ,weight, body mass index, waist /hip ratio 13,14 and blood pressure 17 values because all these factors known to affect the HRV. In present study analysis of HRV by time domain method during normal breathing there was no statistical significant difference in any of the variables between Indians and NRIs.…”
Section: Discussionmentioning
confidence: 66%
“…This test produces a sensitive specific and reproducible indirect measure of autonomic activity on cardiac function In our study the demographic characteristics of the Indians and NRI subjects are well balanced and individuals in both groups did not differ significantly in age 16 ,weight, body mass index, waist /hip ratio 13,14 and blood pressure 17 values because all these factors known to affect the HRV. In present study analysis of HRV by time domain method during normal breathing there was no statistical significant difference in any of the variables between Indians and NRIs.…”
Section: Discussionmentioning
confidence: 66%
“…24 Sevre et al demonstrated a significantly lower BRS in hypertensive subjects than in normotensive controls. 15 Moreover, the reduction in BRS was most pronounced in the female group and did not reach statistical significance in men. BRS was also reduced in hypertensive women compared with hypertensive men.…”
Section: Discussionmentioning
confidence: 89%
“…25-27 These findings imply that hypertensive women are more susceptible to cardiac events and arrhythmias than hypertensive men. 15 During the past several decades, knowledge regarding gender differences in coronary heart disease has been emerging. Annual ischemic heart disease (IHD) population statistics continue to report a greater number of deaths for females than males.…”
Section: Discussionmentioning
confidence: 99%
“…The hypertensive individuals present an increase in the variability of arterial pressure fl uctuation and a decreased sensitivity of the baroreceptors 9,54 . The hypertensive patient's gender also seems to be an important determinant in barorefl ex sensitivity, as the autonomic function shows to be more compromised in the female sex 54 .…”
Section: Factors That Influence the Baroreflex Sensitivitymentioning
confidence: 99%